SAFEGUARDING INNOCENCE: DEVELOPING CURRICULUM OF ISLAMIC SEXUAL EDUCATION IN EARLY CHILDHOOD - Pratiwi, Hardiyanti; Ismail, Murniyanti (Al-Qalam, 2023)
Article 15 of Law No. 35/2014 affirms the right of every child to be protected from various forms of exploitation, including sexual crimes. A well-structured and age-appropriate Islamic sexuality education curriculum plays an important role in shaping a healthy understanding of children's physical, emotional, and social interactions. This research reviews the development of a sexuality education curriculum using the Dick and Carey development model in an Early Childhood Education (ECE) or Kindergarten B unit that refers to the Merdeka Curriculum. This curriculum includes four learning domains, namely intellectual skills, verbal information, psychomotor skills, and attitudes, which are in line with the Learning Outcomes of religious values and character, identity, and the basics of literacy and Steam. The learning design process begins with goal identification through performance analysis and needs assessment, then designing learning objectives that address specific challenges. The curriculum contains two themes, namely Showing Appropriate Reactions to Verbal Harassment and Inappropriate Touching which has 13 learning outcomes and Maintaining Cleanliness and Hygiene of Sensitive Body Parts which has 5 learning outcomes. The media needed to support learning include videos, picture storybooks, cards, snakes and ladders games, puppets, and songs. The appropriate methods are storytelling, socio-drama, interactive games, and discussions. The product was validated by material and curriculum experts. After revision, the values achieved showed improvement,with the Curriculum and Learning Evaluation Expert Assessment increasing from 3.06 to 3.74, reflecting increased suitability and effectiveness. The Early Childhood Sexuality Education Material Content Expert Assessment progressed from 3.08 to 3.67, highlighting improved inclusivity and accuracy.